Pengaruh Citra Merek dan Persepsi Harga terhadap Keputusan Pembelian Sari Roti di Sidoarjo - Anis Nur Laili; Siti Aminah (Universitas KH. Abdul Chalim Mojokerto, 2024)
As the food and beverage industry in Indonesia develops, the competition in this industry is getting tighter and presents new challenges for companies operating in it. This study aims to determine the influence of brand image and price perception on the purchase decision of Sari Roti in Sidoarjo. The population used in this study is Sidoarjo residents who have bought Sari Roti products. The sampling technique uses accidental sampling with a total sample of 100 respondents. Data analysis uses the SEM method by utilizing PLS analysis tools. The results of the study show that brand image and price perception have a positive and significant effect on the purchase decision of Sari Roti in Sidoarjo.